Common Fixed Points of Two Mappings regarding a Generalized c-Distance over a Banach Algebra - Ladan Aryanpour; Hamidreza Rahimi; Ghasem Soleimani Rad (Journal of Function Spaces)
In this article, applying the concept of a generalized c-distance in cone b-metric spaces over Banach algebra with a nonnormal solid cone therein, we establish several common fixed point theorems for two noncontinuous mappings satisfying the Han-Xu-type contraction. Our results are interesting, since they are not equivalent to former well-known results regarding a wt-distance in b-metric spaces while they contain recent results corresponding to a generalized c-distance in cone b-metric spaces.